Wiadomości Bieżące . no. 190, 1981 - Zarząd Regionalny NSZZ "Solidarność" Białystok, ed. Krzysztof Burek, Marian Kałusz (MKZ NSZZ "Solidarność" Region Białystok, 1981)
Creation and circulation: For internal use. - From issue no. 1(16.05.1989) published again legally by Biuro Prasowe NSZZ "Solidarność" Region Białystok